2020
DOI: 10.1093/jas/skaa404
|View full text |Cite
|
Sign up to set email alerts
|

Differential haptoglobin responsiveness to aMannheimia haemolyticachallenge altered immunologic, physiologic, and behavior responses in beef steers

Abstract: Indicator traits associated with disease resiliency would be useful to improve the health and welfare of feedlot cattle. A post hoc analysis of data collected previously (Kayser et al., 2019a) was conducted to investigate differences in immunologic, physiologic, and behavioral responses of steers (N = 36, initial BW = 386 ± 24 kg) that had differential haptoglobin (HPT) responses to an experimentally induced challenge with Mannheimia haemolytica (MH). Rumen temperature, DMI, and feeding behavior data were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…In our trial, the haptoglobin response was not statistically significant, with some animals experiencing a rise in haptoglobin after infection, and others not. A recent post hoc study of feedlot steers challenged with bovine herpesvirus-1 and M. haemolytica revealed that haptoglobin responses were only detectable in 9/18 challenged steers, despite similar body temperatures and clinical disease signs ( Wottlin et al, 2020 ). Interestingly, both the pre- and post-infection feeding behavior patterns were more impacted in haptoglobin-responsive animals compared with the nonresponsive animals, suggesting lower haptoglobin responses may correlate with disease resiliency in feedlot cattle.…”
Section: Discussionmentioning
confidence: 99%
“…In our trial, the haptoglobin response was not statistically significant, with some animals experiencing a rise in haptoglobin after infection, and others not. A recent post hoc study of feedlot steers challenged with bovine herpesvirus-1 and M. haemolytica revealed that haptoglobin responses were only detectable in 9/18 challenged steers, despite similar body temperatures and clinical disease signs ( Wottlin et al, 2020 ). Interestingly, both the pre- and post-infection feeding behavior patterns were more impacted in haptoglobin-responsive animals compared with the nonresponsive animals, suggesting lower haptoglobin responses may correlate with disease resiliency in feedlot cattle.…”
Section: Discussionmentioning
confidence: 99%